2020
DOI: 10.1093/eurpub/ckaa165.124
|View full text |Cite
|
Sign up to set email alerts
|

Digital health literacy in general populations – An international comparison

Abstract: Background Due to the digital transformation in late modern society, digital (or e-) health literacy (DHL) is becoming increasingly relevant for people to take health related decisions. Yet despite its importance for evidence-based policy, very few tools have been developed to measure DHL, and even fewer studies have measured DHL in general populations. The Action Network on Measuring Population and Organizational Health Literacy (M-POHL) is one of the first to include a measure of DHL and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
2
5
0
Order By: Relevance
“…8 Prior examinations have discovered that sufficient levels of DHL relate to better health and quality of health care; positive health behaviors, including prevention and management of chronic diseases; increased procedural health knowledge; and wellbeing. [20][21][22][23] Comparable discoveries reported similar findings among university students in Asia: South Korea, 6 China, 5 Vietnam, 8 and Pakistan. 24 While DHL is essential for students' SWB, scholars have indicated that PM can predict students' DHL.…”
Section: Introductionsupporting
confidence: 54%
See 2 more Smart Citations
“…8 Prior examinations have discovered that sufficient levels of DHL relate to better health and quality of health care; positive health behaviors, including prevention and management of chronic diseases; increased procedural health knowledge; and wellbeing. [20][21][22][23] Comparable discoveries reported similar findings among university students in Asia: South Korea, 6 China, 5 Vietnam, 8 and Pakistan. 24 While DHL is essential for students' SWB, scholars have indicated that PM can predict students' DHL.…”
Section: Introductionsupporting
confidence: 54%
“…This results confirms earlier findings that sufficient or high levels of self-reported DHL relate to better health and more positive health behaviors in the prevention and management of chronic diseases. 6,8,20,22 Since this study appears to be among the first to mediate DHL between PM and SWB, further studies across heterogeneous population are required to broaden knowledge on the linkages established in the current study.…”
Section: Mediation Role Of Dhl In the Relationship Between Pm And Wel...mentioning
confidence: 93%
See 1 more Smart Citation
“…Chew, Cheng, Grant, & Bastidas, 2014 ; Guo et al, 2021 ; Jones, 2013 ; Koopman, Petroski, Canfield, Stuppy, & Mehr, 2014 ; Van der Vaart & Drossaert, 2017 ), they were mostly not used or reworked by other researchers (Griebel et al, 2017 ; Karnoe & Kayser, 2015 ). A new initiative for incorporating eHealth literacy into the measurement of health literacy (Van Den Broucke et al, 2020 ) may both update the assessment of eHealth literacy to include participative activities and yield wider uptake of the tool by the many researchers involved in the initiative.…”
Section: Health Literacy Ehealth Literacy and Their Association With Health Outcomesmentioning
confidence: 99%
“…Since the infodemic increased the state of uncertainty and fear ( 13 ) and negatively affected the strategies adopted to contain the contagion, the role of health literacy (HL), particularly of digital health literacy (DHL), has become crucial. DHL has been defined as a set of skills needed by the individuals to search health information on the Internet, and to understand and apply them to increase awareness and responsibility for one’s own health ( 14 ). The Internet and the social networks are often used by university students as a primary source of health information ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%